Episcopal Power and Personality in Medieval Europe, c . 900– c . 1480 - Coss, Peter; Dennis, Chris; Julian-Jones, Melissa; Silvestri, Angelo (Brepols, 2020)
The question of personality is a problematic one, beset by complications of cultural distance, the layers of the past, and the limitations of the source material. Recognising these difficulties, this volume draws together character sketches based upon historical narratives and a range of sources, including architecture, liturgical manuscripts, chronicles, and hagiographical material, to show a multifaceted range of means by which historians can construct, reconstruct, and deconstruct episcopal power through the person of the bishop. Building on a previous volume of essays, <span class=